Resting hand splint model from topology optimization to be produced by additive manufacturing. Issue 2 (5th September 2021) - Reis, Paulo; Volpini, Mariana; Maia, Joana Pimenta; Guimarães, Igor Batista; Evelise, Cristiane; Monteiro, Maurício; Rubio, Juan Carlos Campos
Abstract : Purpose: The purpose of this study is to validate a novel model of resting hand splint manufactured by additive manufacturing (AM) and compare it with the traditional model manufactured by high temperature thermoplastic in terms of cost, weight, volume and thermal comfort. Design/methodology/approach: A novel resting hand splint model was created from the topology optimization (TO) and analyzed, by finite-element analysis, manufacturing cost and weight, with a traditional resting hand splint. A pilot clinical study was carried out to verify heat diffusion during the use of the two splints. Findings: The results showed that compared with the traditional model, the novel model reduced the volume of material used by 35.48%, the weight of the orthosis by 17.56% and the maximum surface deformation by 171.17% when subjected to actuation forces. It was also verified that, when manufactured with Nylon by AM, the new model is 1.5 times cheaper than the traditional model made of Polypropylene. The result of the thermographic analysis showed greater temperature variation in the use of the traditional splint (+4.6°C) compared to the temperature variation observed in the nylon splint (2.1°C). Practical implications: These results have as clinical relevance the demonstration of the feasibility of manufacturing functional orthoses that are more comfortable, cheaper and lighter than traditional ones. Originality/value: This study describes the use of TO to manufacture a novel resting hand splint, which was compared with the commonly used traditional splint in terms of mechanical resistance, weight, cost and thermal comfort.